The Paris Opera Ballet Dancing Offstage: Work, Grace, and Race. - Nunn, Tessa Ashlin (French Politics, Culture & Society, 2022)
The spaces in which amateur and professional dancers practiced their art greatly changed during the Covid-19 pandemic due to the closures of theaters and dance studios, yet dance continued to bring people together online. This article studies the media presence of the Paris Opera Ballet (POB) between March 2020 and May 2021 to analyze how the aesthetic and moral concept of grace has evolved. During this difficult year, dance took on a therapeutic role as POB dancers offered free online classes and performed in video work, in addition to taking on a political role as discussions about racism in ballet sparked public debates.